تضمين كتب الفقه المدرسية في المرحلة الثانوية بالجمهورية اليمنية للقضايا الفقهية المعاصرة - Abdulqawi Mukred Taresh Al-Qadasi (Universiti Sains Islam Malaysia, 2024)
This research aims to list down the contemporary issues should be included in fiqh schoolbooks in the secondary stag. The current fiqh books will be evaluated according to these issues and recognizing the most prominent fiqh issues that interest the students (male and female). The significance of this study relies on providing a list of the contemporary issues that may benefit the curricula developers when developing the curriculum in the Republic of Yemen. As they currently are working on a comprehensive evaluating and reviewing to develop the curricula. The researcher executes the descriptive approach analyzing the contents of the fiqh books in the secondary school in the Republic of Yemen. The research sample consists of all the fiqh books in the secondary school for the first, second and third grade. The researcher designs a questionnaire comprises 24 contemporary issue related to the Yemeni society and it is so crucial for a student to know the Islamic verdicts on them so he is able to abide the Islamic approach in dealing with these issues. The sample comprises 480 students (half of them female) and the questionnaire is divided into three fields: Ibadat and mu’amalat field (rituals and commercial transactions), politics and behavior field, ahwalshakhsiyyah field (personal status law). The findings reveal that the current fiqh books in Republic of Yemen concludes only 10.5% of the contemporary issues which means its irrelevance to the students’ reality. The study reaches the Yemeni student’s need to study the contemporary issues from his view of point as the result of the questionnaire refers to the consensus of the students (male and female) to include these issues in the fiqh books. One of the most significant recommendations of the research to pay more attention to the fiqh booksin both form and substance. Furthermore, focusing on fulfilling the real needs of the students and to include the contemporary issues in these books or devoting a book for the contemporary issues to be distributed carefully to the students of the secondary school.